KERATONGUIDE – IMPLEMENTASI HARVESINE FORMULA UNTUK MENDETEKSI KEDATANGAN PENGGUNA KETIKA MEMASUKI GEOFENCE - Lim, Yulia; Wasino, Wasino; Perdana, Novario Jaya (Infotech: Journal of Technology Information, 2023)
Keratonguide application is an android-based tour guide application. This application provides features such as tracking travelers' movements in real-time, finding the nearest destination based on tourist locations, displaying information about culinary, hotels, and events based on city choices, and applying the geofence method to display markets based on destination choices. The keratonguide mobile application uses the flutter framework with the programming language using dart, integrates the Google Maps API to draw a polyline from the tourist position to the destination based on the tourist's choice and also implements the Harvesine Formula to find the nearest destination. The final result of this research is that users can choose the destination they want to visit and get information about the market when entering the radius based on the selected destination using the geofencing method.